2020
DOI: 10.1136/bmjopen-2020-038128
|View full text |Cite
|
Sign up to set email alerts
|

Role of probiotics in patients with colorectal cancer: a systematic review protocol of randomised controlled trial studies

Abstract: IntroductionColorectal cancer is one of the leading causes of cancer-related morbidity worldwide and it has been reported to be associated with poor lifestyle habits which include excess tobacco and alcohol intake as well as genetics and age factors. Probiotics such as the lactic acid bacteria and Bifidobacterium as well as probiotic containing foods (kombucha, kefir, miso etc) have received lots of attention as anticancer agents for prevention and treatment. The effects of the administration of probiotics to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 31 publications
0
3
0
Order By: Relevance
“…Some microorganisms can suppress the progression and metastasis of CRC [83][84][85][86]. For instance, several probiotics have the potential to decrease DNA damage and inflammation.…”
Section: Gut Microbiota and Crcmentioning
confidence: 99%
“…Some microorganisms can suppress the progression and metastasis of CRC [83][84][85][86]. For instance, several probiotics have the potential to decrease DNA damage and inflammation.…”
Section: Gut Microbiota and Crcmentioning
confidence: 99%
“…Probiotics have long been marketed to the general public as a dietary supplement for their potential beneficial effects on the gut[ 66 ]. The replenishment of beneficial intestinal microbial communities may help stimulate epithelial cell proliferation, reduce pathogenic overgrowth, ameliorate gut inflammation, and potentially reduce the risk of CRC[ 67 - 69 ]. Studies have also shown that certain strains of probiotics may be effective as an adjuvant agent to CRC treatment[ 70 ].…”
Section: Gut Microbiomementioning
confidence: 99%
“…Previous systematic reviews have examined the impact of prebiotics and probiotics on gut microbial or CRC outcomes, including colonic inflammatory markers, microbial diversity, and postoperative complications after CRC resection [13][14][15][16]. However, no reviews to date have focused on the effect of prebiotic and probiotic supplementation on incidence of colorectal neoplasia in population-based studies.…”
Section: Introductionmentioning
confidence: 99%